Impact of Treated Wastewater on Soil and Crops Irrigated Using Drip and Sprinkler Systems - Rawashdeh, Rola N.; Abu-Awwad, Ahmad M.; Tabbaa, Mohammad J. (Jordan Journal of Agricultural Sciences, 2021)
The Jordanian standards (JS893/2006) governing the reuse of treated wastewater (TWW) in agricultural irrigation only permit the use of drip and/or surface irrigation, and ban Sprinkler irrigation usage except for golf fields, and only during the night. This research was conducted to investigate the impact of using drip and sprinkler irrigation systems using TWW on soil nutrients and crop quality. Three fields were irrigated with TWW (i) Alfalfa using sprinkler (AS), (ii) Barley using sprinkler (BS), and (iii) Barley using drip (BD). To give a comparison, another barley field received only rainwater (BR). Results showed that no E. coli was detected (< 3 MPN/gm) on the plants (alfalfa and barley) irrigated with TWW using either drip or sprinkler. The negligible presence of E. coli, if any, in the middle and lower parts of the alfalfa plant could be attributed to the sampling time and the dense leaf of alfalfa. Results revealed that irrigation systems have no significant effect on soil chemical properties. However, the effect of TWW on soil chemical properties was significant. The significant increase in soil chemical properties could be attributed to the TWW content and the amount of its usage.